MicroRNAs Regulating Tumor Immune Response in the Prediction of the Outcome in Patients With Breast Cancer - Thomopoulou, Konstantina; Papadaki, Chara; Monastirioti, Alexia; Koronakis, George; Mala, Anastasia; Kalapanida, Despoina; Mavroudis, Dimitrios; Agelaki, Sofia (Frontiers in Molecular Biosciences, 2021)
MicroRNAs (miRNAs) are key regulators in immune surveillance and immune escape as well as modulators in the metastatic process of breast cancer cells. We evaluated the differential expression of plasma miR-10b, miR-19a, miR-20a, miR-126 and miR-155, which regulate immune response in breast cancer progression and we investigated their clinical relevance in the outcomes of breast cancer patients. Plasma samples were obtained from early (eBC; n=140) and metastatic (mBC; n=64) breast cancer patients before adjuvant or first-line chemotherapy, respectively. Plasma miRNA expression levels were assessed by qRT-PCR. We revealed a 4-miRNA panel consisted of miR-19a, miR-20a, miR-126 and miR-155 able to discriminate eBC from mBC patients with an AUC of 0.802 (p<0.001). Survival analysis in eBC patients revealed that low miR-10b and miR-155 expression was associated with shorter disease free survival (DFS; p=0.012 and p=0.04, respectively) compared to high expression. Furthermore, miR-126 expression was associated with shorter overall survival (OS; p=0.045). In multivariate analysis the number of infiltrated axillary lymph nodes and low miR-10b expression independently predicted for shorter DFS (HR: 2.538; p=0.002 and HR: 1.943; p=0.033, respectively) and axillary lymph nodes and low miR-126 for shorter OS (HR: 3.537; p=0.001 and HR: 2.558; p=0.018). In the subgroup of triple negative breast cancer (TNBC) patients, low miR-155 expression independently predicted for shorter DFS (HR: 5.056; p=0.037). Accordingly in mBC, patients with low miR-10b expression had shorter PFS and OS compared to patients with high expression (p=0.0017 and p=0.042, respectively). In multivariate analysis, recurrent disease and low miR-10b expression independently predicted for shorter PFS (HR: 2.657; p=0.001 and HR: 1.920; p=0.017, respectively), whereas performance status 2 independently predicted for shorter OS (HR: 2.031; p=0.03). In summary, deregulated expression of circulating miRNAs involved in tumor and immune cell interactions evaluated before adjuvant and 1st-line chemotherapy can distinguish disease status and emerge as independent predictors for outcomes of breast cancer patients.